1989
DOI: 10.1037/0033-2909.106.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive feedback on performance.

Abstract: This presents a comprehensive review of the empirical literature bearing on the effects of cognitive feedback (CFB) on multiple measures of performance. CEB refers to the process of presenting the person information about the relations in the environment (task information [TI]), relations perceived by the person (cognitive information [CIj), and relations between the environment and the person's perceptions of the environment (functional validity information [FVI]). Overall, CFB does improve performance on jud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
288
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(302 citation statements)
references
References 73 publications
9
288
5
Order By: Relevance
“…(Balzer et al,1989) and this result has been found to apply in the forecasting context (Remus et al,1996). Indeed, outcome feedback may actually damage performance by drawing attention to the most recent observation (which will contain noise) and thereby accentuating the tendency to overweight this observation in the subsequent forecast.…”
Section: ) Providing Learning Facilitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…(Balzer et al,1989) and this result has been found to apply in the forecasting context (Remus et al,1996). Indeed, outcome feedback may actually damage performance by drawing attention to the most recent observation (which will contain noise) and thereby accentuating the tendency to overweight this observation in the subsequent forecast.…”
Section: ) Providing Learning Facilitiesmentioning
confidence: 94%
“…due to promotion activity). Feedback can take a number of forms (Benson and Onkal,1992;Balzer et al,1989) including:…”
Section: ) Providing Learning Facilitiesmentioning
confidence: 99%
“…In the double-system design, the parameters of the ecological side of the lens model are known (see Figure 1). This design has been used to study achievement or judgment accuracy (Hammond, 1955), multiple-cue probability learning (Hammond & Summers, 1965;Klayman, 1988), and cognitive feedback (Balzer, Doherty, & O'Connor, 1989;F. J. Todd & Hammond, 1965).…”
Section: Social Judgment Theory Policy Capturing and The Importancementioning
confidence: 99%
“…It has been recognized that efficacy is not the only important criterion in the evaluation of a novel application. Of equal importance is users' subjective impressions, since if people do not have a favorable reaction to the application, they will not use it anyway (e.g., Balzer et al, 1989). The users' interaction with the program was measured by means of video observation, and their subjective reactions were measured by a questionnaire.…”
Section: The Present Studymentioning
confidence: 99%